Trait matching and phenological overlap increase the spatio‐temporal stability and functionality of plant–pollinator interactions - Peralta, Guadalupe; Vázquez, Diego P.; Chacoff, Natacha P.; Lomáscolo, Silvia B.; Perry, George L. W.; Tylianakis, Jason M.; Irwin, Rebecca (Ecology letters, 2020)
Morphology and phenology influence plant–pollinator network structure, but whether they generate more stable pairwise interactions with higher pollination success remains unknown. Here we evaluate the importance of morphological trait matching, phenological overlap and specialisation for the spatio‐temporal stability (measured as variability) of plant–pollinator interactions and for pollination success, while controlling for species' abundance. To this end, we combined a 6‐year plant–pollinator interaction dataset, with information on species traits, phenologies, specialisation, abundance and pollination success, into structural equation models. Interactions among abundant plants and pollinators with well‐matched traits and phenologies formed the stable and functional backbone of the pollination network, whereas poorly matched interactions were variable in time and had lower pollination success. We conclude that phenological overlap could be more useful for predicting changes in species interactions than species abundances, and that non‐random extinction of species with well‐matched traits could decrease the stability of interactions within communities and reduce their functioning. Morphology and phenology influence plant‐pollinator network structure, but whether they generate more stable pairwise interactions with higher pollination success is unknown. We show that interactions among abundant plants and pollinators with well‐matched traits and phenologies formed the stable and functional backbone of the pollination network, whereas poorly‐matched interactions were variable in time and had lower pollination success.